E-Cadherin Expression in Canine Melanocytic Tumors: Histological, Immunohistochemical, and Survival Analysis. Issue 5 (September 2020) - Silvestri, Serenella; Porcellato, Ilaria; Mechelli, Luca; Menchetti, Laura; Iussich, Selina; De Maria, Raffaella; Sforna, Monica; Bongiovanni, Laura; Brachelente, Chiara
E-cadherin, a glycoprotein involved in cell-cell adhesion, has a pivotal role in epithelial-mesenchymal transition, a process through which neoplastic epithelial cells develop an invasive phenotype. In human cutaneous melanomas, decreased E-cadherin expression is associated with shorter survival and increased Breslow thickness, whereas in the dog its role is poorly understood. Tumor thickness and modified Clark level were recently proposed as useful features to assess canine melanocytic tumors, but no studies investigated their association with E-cadherin expression. We performed immunohistochemistry on 77 formalin-fixed, paraffin-embedded primary canine melanocytic tumors. A 3-tier and a 2-tier classification system for assessing E-cadherin expression were tested, with the latter being more informative for the assessment of canine melanocytic tumors. E-cadherin expression was lower in cutaneous melanomas than melanocytomas, as well as in amelanotic tumors compared to pigmented tumors. In amelanotic melanomas, absent E-cadherin expression was associated with an unfavorable outcome, suggesting a potential use of this marker in defining the prognosis of amelanotic melanomas. E-cadherin expression was lower in tumors with greater tumor thickness and modified Clark level ≥IV, suggesting its possible utility in identifying the most invasive tumors. The expression of E-cadherin in oral melanomas was heterogeneous, but was associated with pigmentation and clinical outcome; thus, E-cadherin evaluation could be advantageous to detect the most aggressive neoplasms. However, cutaneous melanomas without E-cadherin expression frequently had a favorable clinical outcome. Hence, its importance as prognostic factor should be carefully considered depending on the tumor origin.